DIGITAL STORYTELLING AS POLITICAL IMAGE CONSTRUCTION IN THE 2024 PRESIDENTIAL ELECTION CAMPAIGN: CASE STUDY OF THE TIKTOK ACCOUNT @GIBRAN_RAKABUMING - Radians Krisna Febriandy; Prabu Revolusi (Bajang Institute, 2024)
This research discusses the use of digital storytelling as a political image on Gibran Rakabuming Raka's TikTok account in the 2024 presidential election. The research uses a qualitative approach with the content analysis method. The research focuses only on the TikTok account @gibran_rakabuming, as of April 4, 2024, which has 3.3 million followers, 41.2 million likes, and 782 video uploads. This research was then categorized into nine (9) types of political image quantification videos based on research by Muksin et al (2023). The results showed that there were two (2) most video categories during the 2024 presidential election campaign period, namely art, music & sports and close to the community. Keywords: Digital storytelling; Political Image; Social Media; 2024 Presidential Election Campaign; TikTok. Digital storytelling; Political Image; Social Media; 2024 Presidential Election Campaign; TikTok